A decision-making method for reservoir operation schemes based on deep learning and whale optimization algorithm - Hu, Qiang; Hu, He-xuan; Lin, Zhen-zhou; Chen, Zhi-hao; Zhang, Ye (Frontiers in Plant Science, 2023)
Reservoir operation is an important part of basin water resources management. The rational use of its scheme can not only enhance the capacity of flood control and disaster reduction in the basin, but also improve the efficiency of water use and give full play to the comprehensive utilization benefits of the reservoir. Aiming at the problems of large computation, subjectivity and difficulty in capturing nonlinear relationships in conventional reservoir operation scheme decision-making methods, this paper proposes a reservoir operation scheme decision-making model IWGAN-IWOA-CNN based on artificial intelligence and deep learning technology. In view of the lack of data in the original reservoir operation scheme and the limited improvement of data characteristics by the traditional data augmentation algorithm, an improved generative adversarial network algorithm (IWGAN) is proposed. IWGAN uses the loss function which integrates Wasserstein distance, gradient penalty and difference item, and dynamically adds random noise in the process of model training. The whale optimization algorithm is improved by introducing Logistic chaotic mapping to initialize population, non-linear convergence factor and adaptive weights, and Levy flight perturbation strategy. The improved whale optimization algorithm (IWOA) is used to optimize hyperparameters of convolutional neural networks (CNN), so as to obtain the best parameters for model prediction. The experimental results show that the data generated by IWGAN has certain representation ability and high quality; IWOA has faster convergence speed, higher convergence accuracy and better stability; IWGAN-IWOA-CNN model has higher prediction accuracy and reliability of scheme selection.